Exploring the structure and electronic properties of germanium doped boron clusters using density functional theory based global optimization method - Anis, Insha; Dar, Mohd Saleem; Rather, Ghulam Mohammad; Dar, Manzoor Ahmad (New Journal of Chemistry, 2022)
Density functional theory calculations in the framework of B3LYP, TPSS and M06-L were carried out to investigate the effect of single and double germanium atom doping on the geometric structure and electronic properties of boron clusters with 10 to 20 atoms. Global minima of GeBn and Ge2Bn (n = 10-20) were first obtained through Crystal Structure Analysis by the Particle Swarm Optimization method and then subsequently optimized using meta-generalized gradient approximation, hybrid and local functionals. It is found that the lowest energy structures of GeBn and Ge2Bn clusters exhibit planar, quasi-planar, semi-cage, bowl, and double ring topologies. Like BnSi clusters, the results reveal that the germanium atom prefers the peripheral regions of the B-n framework contrary to transition metal doped boron clusters. Furthermore, the calculated electronic properties such as the average binding energy and second order difference in binding energy indicate GeB20 and Ge2B16 to be the most stable clusters. Molecular orbital and adaptive natural density partitioning analyses were carried out to understand the extra stability of GeB20 and Ge2B16 clusters.

First-principles investigation of the electrocatalytic reduction of CO2 on zirconium-based single-, double-, and triple-atom catalysts anchored on a graphitic carbon nitride monolayer - Hassan, Afshana; Anis, Insha; Shafi, Sadaf; Assad, Assif; Rasool, Anjumun; Khanam, Romana; Bhat, Gulzar Ahmad; Krishnamurty, Sailaja; Dar, Manzoor Ahmad (ACS Applied Nano Materials, 2022)
Conversion of carbon dioxide (CO2) with the help of an appropriate electrocatalyst with high stability, low onset potential, and exceptional selectivity is still one of the great tasks in the electrocatalytic reduction of CO2 to valuable chemicals. Herein, by means of systematic first-principles simulations, we investigate the CO2 reduction reaction (CO2RR) activity of zirconium-based single-, double-, and triple-atom (Zrn@C2N; n = 1-3) catalysts anchored on a graphitic carbon-nitride monolayer. In tune with the Sabatier principle, our results reveal that a moderate CO2 binding is vital for a low onset potential for the CO2RR. Consequently, based on rigorous free energy calculations, the Zr-based single-atom catalyst (SAC) is found to be most effective to convert CO2 to valuable products such as HCOOH and CH3OH. It is worth noting that CO2 reduction to HCOOH is spontaneous via the *HCOO intermediate on Zr1@C2N and involves a low onset potential of -0.23 V with respect to the reversible hydrogen electrode from the *COOH intermediate. Among all the catalysts evaluated computationally, the Zr SAC further reveals the lowest onset potential of -0.89 V for CH3OH formation. The results show that the Zr-based catalysts especially Zr1@C2N are found to effectively suppress the competitive hydrogen evolution reaction and promote the CO2RR. Moreover, all three catalysts exhibit high kinetic and thermal stability with negligible distortion due to which their structures can be retained very well up to 600 K. Thus, the current work may provide effective catalyst-design strategies for enhancing the electrocatalytic CO2RR performance of Zr-based materials.
Keywords: C1 and C2 products; CO2 reduction; first-principles simulations; hydrogen evolution reaction; onset potential; single-atom catalysts (SACs); Zrn@C2N catalysts

Probing the site-specific reactivity and catalytic activity of Ag-n (n=15-20) silver clusters - Anis, Insha; Dar, Mohd Saleem; Bhat, Gulzar Ahmad; Rather, Ghulam Mohammad; Dar, Manzoor Ahmad (ACS Omega, 2022)
Density functional theory calculations within the framework of generalized gradient approximation (GGA), meta-GGA, and local functionals were carried out to investigate the reactivity and catalytic activity of Ag-n (n = 15-20) clusters. Our results reveal that all the Ag-n dusters in this size range, except Ag-20, adsorb O-2 preferably in the bridged mode with enhanced binding energy as compared to the atop mode. The O-2 binding energies range from 0.77 to 0.29 in the bridged mode and from 0.36 to 0.15 eV in the atop mode of O-2 adsorption. The strong binding in the case of the bridged mode of O-2 adsorption is also reflected in the increase in O-O bond distance. Natural bond orbital charge analysis and vibrational frequency calculations reveal that enhanced charge transfer occurs to the O-2 molecule and there is significant red shift in the stretching frequency of O-O bond in the case of the bridged mode of O-2 adsorption on the clusters, thereby confirming the above results. Moreover, the simulated CO oxidation reaction pathways show that the oxidation of the CO molecule is highly facile on Ag-16 and Ag-18 clusters involving small kinetic barriers and higher heats toward CO2 formation.

Tantalum based single, double, and triple atom catalysts supported on g-C2N monolayer for effective nitrogen reduction reaction: a comparative DFT investigation - Rasool, Anjumun; Anis, Insha; Dixit, Mudit; Maibam, Ashakiran; Hassan, Afshana; Krishnamurty, Sailaja; Dar, Manzoor Ahmad (Catalysis Science & Technology, 2022)
Design of efficient and low cost electrocatalysts for the reduction of N-2 molecule to NH3 in a green manner remains a great challenge in the 21st century. Herein, we have used density functional theory based first principle simulations to systematically investigate the nitrogen reduction reaction (NRR) ability of single, double, and triple Ta-atom catalysts anchored to C2N monolayer. Our results demonstrate that the single and triple Ta-atom catalysts anchored to C2N monolayer act as superior catalysts for the NRR via alternating and distal pathways as compared to the Ru(0001) stepped surface. In particular, the triple Ta-atom catalyst anchored to C2N shows enhanced NRR performance with a limiting potential of -0.72 V which is comparable to the experimentally reported Ru based single atom catalyst. Further, all the three catalysts were found to be highly selective for NRR with an enhanced ability to suppress the competitive hydrogen evolution reaction. Electronic structure analysis revealed that the enhanced ability of Ta-3@C2N catalyst to effectively capture and reduce N-2 molecule could be attributed to the built up of localized d states near the fermi level, thereby aiding in strong electron transfer into the antibonding orbitals of N-2. Thus, our findings propose a highly active catalyst for the NRR with an emphasis on the importance of triple atom-based catalysts for electrocatalytic applications.